MECHANISMS OF ORAL CAVITY TISSUES STRESS DAMAGES (A BRIEF REVIEW OF THE LITERATURE AND OUR OWN RESEARCH) - L.M. Tarasenko; M.V. Bilets (Український стоматологічний альманах, 2018)
The article briefly discusses the mechanisms of stress damage of oral cavity tissues.